2021
DOI: 10.1116/6.0001042
|View full text |Cite
|
Sign up to set email alerts
|

Optical realization of the pascal—Characterization of two gas modulated refractometers

Abstract: By measuring the refractivity and the temperature of a gas, its pressure can be calculated from fundamental principles. The most sensitive instruments are currently based on Fabry–Perot cavities where a laser is used to probe the frequency of a cavity mode. However, for best accuracy, the realization of such systems requires exceptional mechanical stability. Gas modulation refractometry (GAMOR) has previously demonstrated an impressive ability to mitigate the influence of fluctuations and drifts whereby it can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Since the instrumentation scrutinized in this work has been assessed to have an extended uncertainty of − + [3], this scrutiny, which has concluded that the influence of thermodynamic effects on the assessment of pressure when 100 kPa of nitrogen is addressed is in the sub-ppm level, has indicated that, despite the use of gas modulation cycle times of 200 s, as can be used when the GAMOR method is utilized, the Invar-based DFPC system is not significantly affected by thermodynamic effects related to the gas exchange process. Hence, this work further strengthens the conclusion that thermodynamic effects (pV-work) will not be a limiting factor when the Invar-based DFPC GAMOR system is used for assessments of pressure or as a primary pressure standard for pressures up to 100 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…Since the instrumentation scrutinized in this work has been assessed to have an extended uncertainty of − + [3], this scrutiny, which has concluded that the influence of thermodynamic effects on the assessment of pressure when 100 kPa of nitrogen is addressed is in the sub-ppm level, has indicated that, despite the use of gas modulation cycle times of 200 s, as can be used when the GAMOR method is utilized, the Invar-based DFPC system is not significantly affected by thermodynamic effects related to the gas exchange process. Hence, this work further strengthens the conclusion that thermodynamic effects (pV-work) will not be a limiting factor when the Invar-based DFPC GAMOR system is used for assessments of pressure or as a primary pressure standard for pressures up to 100 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…A close scrutiny of the Invar-based system has revealed that the system is capable of assessing pressure with an extended uncertainty (k = 2) of [(10 mPa) 2 + (10 ×10 −6 P) 2 ] 1/2 [18], which is in pair with the so far, most accurate FP-refractometry system developed by NIST.…”
Section: Wp1: Pressure Measurements Based Onmentioning
confidence: 91%
“…The refractometry system, denoted the Transportable Optical Pascal (TOP), has previously been described in detail [3], [4]. Besides a brief IMEKO 24 th TC3, 14 th TC5, 6 th TC16 and 5 th TC22 International Conference 11 -13 October 2022, Cavtat-Dubrovnik, Croatia 2 of 7…”
Section: The Transportable Refractometermentioning
confidence: 99%
“…The system differs from a previously constructed stationary system (SOP) [3], [5], [7] primarily by the way the temperature is assessed; instead of assessing the temperature with respect to a Ga fixed point cell, it utilizes calibrated Pt-100 sensors. This contributes to its uncertainty by 20 parts-permillion, which is on par with the uncertainties of pressure balances used in the circular comparison.…”
Section: System Detailsmentioning
confidence: 99%
See 1 more Smart Citation